Susceptibility of Type I Interferon Receptor Knock-Out Mice to Heartland Bandavirus (HRTV) Infection and Efficacy of Favipiravir and Ribavirin in the Treatment of the Mice Infected with HRTV - Fujii, Hikaru; Tani, Hideki; Egawa, Kazutaka; Taniguchi, Satoshi; Yoshikawa, Tomoki; Fukushi, Shuetsu; Yamada, Souichi; Harada, Shizuko; Kurosu, Takeshi; Shimojima, Masayuki; Maeki, Takahiro; Lim, Chang-Kweng; et al. (Viruses, 2022)
Heartland bandavirus (HRTV) is an emerging tick-borne virus that is distributed in the United States and that causes febrile illness with thrombocytopenia and leukocytopenia. It is genetically close to Dabie bandavirus, which is well known as severe fever with thrombocytopenia syndrome (SFTS) virus (SFTSV). The mortality rate of human HRTV infection is approximately 10%; however, neither approved anti-HRTV agents nor vaccines exist. An appropriate animal model should be developed to evaluate the efficacy of antiviral agents and vaccines against HRTV. The susceptibility of IFNAR−/− mice with HRTV infection was evaluated using subcutaneous, intraperitoneal, and retro-orbital inoculation routes. IFNAR−/− mice intraperitoneally infected with HRTV showed the most severe clinical signs, and the 50% lethal dose was 3.2 × 106 TCID50. Furthermore, to evaluate the utility of a novel lethal IFNAR−/− mice model, IFNAR−/− mice were orally administered favipiravir, ribavirin, or a solvent for 5 days immediately after a lethal dose of HRTV inoculation. The survival rates of the favipiravir-, ribavirin-, and solvent-administered mice were 100, 33, and 0%, respectively. The changes in bodyweights and HRTV RNA loads in the blood of favipiravir-treated IFNAR−/− mice were the lowest among the three groups, which suggests that favipiravir is a promising drug candidate for the treatment of patients with HRTV infection.